PP66 Increasing Burden Of Out-Of-Pocket Healthcare Expense On Patients. (2019) - Arora, Rhythm; Dugar, Nikhil; Saxena, Vandit; Jaiswal, Sunil K.; Kumari, Chitresh; Cook, Nigel; Furio, Olga
Abstract : Introduction: We conducted an analysis of the key factors triggering cost-sharing mechanisms to understand the status of out-of-pocket (OOP) healthcare expense in the United States (US), Europe, and emerging markets and better appreciate the implications of OOP healthcare expense on patients' health management. Methods: A review of literature and databases including The Organisation for Economic Co-operation and Development (OECD) and World Bank was performed to understand different cost-sharing mechanisms, factors triggering OOP expenditure and the country-wise trends of OOP expenditure. Additionally, the impact of OOP expenditure on healthcare budget and on patients in terms of medication adherence, uptake of newer therapies and generic substitution was explored. Results: The findings reveal that patients are concerned about rising healthcare OOP costs, and we observed an increase of 134 percent in the number of articles published on OOP from 2005 to 2017. The percentage of household spending that goes OOP as healthcare expense is higher in Brazil, Russia, India, and China (BRIC countries; ~11 percent) compared to France, Germany, Italy, United Kingdom, US, Japan, and Canada (G7 countries; ~2 percent). In addition, OOP expenditure increased with age (1.9 percent of take home income in 55-64 age group versus 1.2 percent in 18-25 age group) and is higher in the low-income population (2.8 percent of take home income versus 1 percent in high-income group). Whereas, increasing OOP expenditure reduces the overall healthcare expenditure due to generic substitution (28 percent reduction) and reduction in excessive consumption of supplementary medicines, it also reduces patient adherence (~20 percent decline in dispensed prescriptions) and may foster a reluctance to adopt newer therapies. Conclusions: The population groups most impacted by increasing OOP expense are the older population, those in the low-income bracket and in poorer countries. While OOP expense may help in the effective and judicious utilization of healthcare system resources and medicines usage, its implementation requires a cautious and considered approach.